Investigating the Impact of Supply Chain Practices on the Financial Performance of Active Firms in Egyptian stock Market - Youssef, Amr E.; El-Nakib, Islam (International Journal of Supply Chain Management, 2015)
Managing supply chain is one of the big tasksfor enterprises with sustaining the competitive advantages that reflected intheir bottom-line financial figures. Therefore, this research aims at exploringthe impact of supply chain practices i.e. supply chain integration, complexitymanagement, aligning strategy and supply chain, IT with process improvement,and operational innovation on the financial performance i.e.  Return onAssets (ROA) and Return of Equity (ROE) of different manufacturing companies inthe Egyptian market. Qualitative and quantitative approaches have been followedto use theories and literature to cover the supply chain concepts and practicesin order to test it empirically. In addition, research data was collected from98 managers who are representing 14 manufacturing companies, which areregistered in the market of Egypt Stock Exchange from the year 2005 to 2010. Inaddition, secondary data on financial performance of the participated companieswere obtained from their websites and/or other publications. Research findingsindicate a strong relationship between supply chain practices and bottom-lineprofits of an organization. In addition, the supply chain managers decrease theuse of large fixed assets such as plants, warehouses and transportationvehicles in the supply chain. Results yield useful insights to both academics,and corporate practitioners about the importance of synthesizing supply chainwith financial performance.